Phase composition and morphology of nanostructured coatings deposited by laser dispersion of a mixture of polyethylene with iron oxalate; Вестник Карагандинского университета. Серия Физика; № 3 (99) - Rudenkov A. S. Aleksandr; Yarmolenko M. A.; Rogachev A. A.; Surzhikov A. P. Anatoly Petrovich; Luchnikov A. P. Aleksandr Petrovich; Frolova O. A. Oksana Aleksandrovna (2020, 2020)
Peculiarities of forming of iron oxide coatings with reinforced carbon nanostructures from gas phase generated by laser dispersion of composite target were explored. Influence of technological modes of heat treatment on morphology and phase composition of nanostructured film layers was determined. It was found that on a substrate highly dispersed layers containing carbon nanostructures are formed. Using Raman spectroscopy it was shown that in oxide matrix carbon structures, which are mainly in the form of planar located nanotubes, appear. It was found that with a mass ratio of polyethylene and iron oxalate equal to 1:1, the distribution of the formed nanostructures in size is unimodal with a maximum near 20 nm. At dispersing of polyethylene and iron oxalate mixture with mass ratio 1:2 in deposited layers nanotubes have the least defectiveness. Patternsof influence on morphology and coatings phase composition of relative component abundance in being dispersed by laser radiation composite target were determined. It was shown that with the growing of iron oxalate concentration in the target coating structural heterogeneity increases, subroughness and average size of separate nanostructures in the deposited condensate grow. The obtained polymer matrix nanocomposite films can be used in sensors.